Investigation of the Electron Coefficients of (Ar, He, N2, O2) Gases in the Ionosphere - Aseel A. Temur; Ala F. Ahmed (مجلة بغداد للعلوم)
In this study, the electron coefficients; Mean energy , Mobility and Drift velocity  of different gases  Ar, He, N2 and O2  in the  ionosphere have been calculated using BOLSIG+ program to check the solution results of Boltzmann equation results, and effect of reduced electric field (E/N) on electronic coefficients. The electric field has been specified in the limited range 1-100 Td. The gases were in the ionosphere layer at an altitude frame 50-2000 km. Furthermore, the mean energy and drift velocity steadily increased with increases in the electric field, while mobility was reduced. It turns out that there is a significant and obvious decrease in mobility as a result of inelastic collisions and in addition little energy gained by the reduced electric field. A clear mathematical model was obtained to find out the electronic coefficient values without a simulation program (BOLSIG +). In addition, this model shows a strong correlation between the current work and the electronic transaction values calculated through the BOLSIG+ program.